Posted by **Trista** on Saturday, April 7, 2007 at 3:56pm.

Given f(x) = –x3 + x2 – x – 5, find f(–3), f(0), and f(1)

Hmmmm. Put in the value of x, and compute.

Here is f(0) as an example:

f(0)=-0^3 + 0^2 -0 -5 = -5

## Answer This Question

## Related Questions

- Math - Here is the problem: Compute the value of the given expression: - | -8...
- math - Compute f '(a) algebraically for the given value of a. HINT [See Example ...
- calculus - consider the initial value problem dy/dx=y^2+1, y(0)=0. estimate y(2...
- math, functions - f(x) = 1/(1−x) is given. From this we produce two new ...
- math - I am having to find the value of y for the given values of x. I ...
- m ath - Compute f '(a) algebraically for the given value of a. HINT [See Example...
- Functions - f(x) = 1/(1−x) is given. From this we produce two new ...
- derivatives - Compute f '(a) algebraically for the given value of a. HINT [See ...
- math - Compute f '(a) algebraically for the given value of a f(x) = x3 + 8x; a...
- Math - The question is compute the value of the given expression. -|-15|-|21|. ...

More Related Questions